Translation Analysis of Negative Sentences in the Zakat Chapter of the Book Al-Fiqh Al-Muyassar - Kusumadewi, Justicia Shabirina; Anis, Muhammad Yunus; Mohammed, Chouchani Abidi (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
In fiqh books, the translation of negative sentences into Arabic plays a crucial role in accurately explaining Islamic laws. This phenomenon requires translators to pay attention to correct grammatical structures and the use of appropriate technical terms within the context of Islamic law. For example, negative statements that indicate prohibition or disapproval (makruh) must be translated precisely to prevent misunderstandings or mistaken readings. This study aims to analyzes al-jumlah al-manfiyyah in Arabic, translation techniques, and the quality in al-fiqh al-muyassar. Using a descriptive qualitative approach with Spradley's analysis, 93 instances were identified, employing 12 translation techniques. Of these, 82 were accurately translated with high readability, resulting in a final quality score of 2.83. This suggests that readers can comprehend fiqh worship texts and muamalat effectively. Thus, this research significantly advances scholarship in Arabic language research by setting benchmarks for precision and comprehensibility in translating Islamic legal texts. Future researchers should explore the subtleties of interpreting negative sentences in fiqh texts, consider cultural and contextual influences on Islamic legal texts, and establish standardized guidelines for accurate and accessible translations.